สภาวะการทำงานและความเครียดของบุคลากรฝ่ายโภชนวิทยาและโภชนบำบัด โรงพยาบาลจุฬาลงกรณ์ - พรประภา ม่วงเจริญ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purpose of this Cross-sectional Descriptive Study was to find out the relationship between the working condition and work related stress among staffs of the Department of Dietetics and Diet therapy, King Chulalongkorn Memorial Hospital. Population sample were one hundred ninety we study all of the department. The research instruments were demographic questionnaire, work factors questionnaire, and occupational stress and burnout questionnaire, translated by Professor Nantika Thavichachart. Data were analyzed by descriptive statistics, chi-square test and multiple regression analysis. The results of the study showed that the majority of staffs were female (73.7%), the mean age was 39.7 years, high school of education (33.2%), the mean monthly income was 11,213.63 baht (n = 171), the mean time on the job was 13.10 years (n = 184), the majority of position were employees (68.4%). the prevalence of stress at work and burnout were 12.1% and 4.7 % respectively. Stress at work was significantly associated with demographic factors includes educational level, monthly income (p<0.001), caffeine consumption (p < 0.01), alcohol consumption, family burden, check up, diseases, Injury or illness, and exercise (p < 0.05). Stress at work were variably associated with work factors includes time on the job, position job, temperature (p<0.01), shift work, difficult task (work itself and role) were significantly associated with stress (p<0.05), stuffiness, inconvenience and sound were significantly associated with stress (p<0.001), sleep were inversely associated with stress (p<0.01). Stress at work was significantly associated with confidence of supervisor in my work, Job match skills and being interested (supervisor relationships), strategic direction, understand of role and function (work itself and role) (p < 0.01), supervisor’s support, freedom to express to supervisor (supervisor relationships) , helpful co-worker (co-worker relationship) , possibility of growth(advancement and job security) (p < 0.05), performance appraisal (advancement and job security), medical expenses, overtime pay, salary increase appropriate, salary for the position and workload (welfare and Reward), high-level supervisors listen and solve, human resource management, policies company, communication, and promotion (policy and administration) (p<0.001). eight predictive variables of occupational stress were confidence of supervisor in my work, helpful co-worker, communication, exercise, overtime work payment, promotion, sleep, and educational level.